Economic and Social Determinants of Mexican Circular and Permanent Migration - Jorge Eduardo Mendoza (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2008)
This study seeks to determine the factors that have impacted the duration of the Mexican temporary and permanent migrant trips to the United States. The explanatory variables consist of socioeconomic factors, human capital, migration experience, social capital and labor variables. The data collected between 1987 and 2007 showed that more than half of the Mexican migrants that enter the USA did not have documents and that social networks are an important factor determining migrant trip duration. Also, the restrictive USA migration policies since 2001 have negatively affected migrant trip duration. A logit model of migrant trip duration determinants is estimated. The results showed that gender becomes more important for trips of more than five years; also married migrants are likely to stay on a permanent basis. Labor skills and education coefficients and the use of coyotes have become increasingly important and their coefficients imply a higher probability for longer trips. The dummy variable for anti-immigration policy showed a higher probability for permanent migration, reflecting difficulties in crossing the border.